In vitro antioxidant, anti-inflammatory activities and acetylcholinesterase inhibition properties of selected plant extracts - Katarzyna Jakimiuk; Daniel Augustynowicz; Sylwia Wojtulewicz; Wiktoria Wiśniewska; Jakub Władysław Strawa; Julia Wyszkowska; Michał Tomczyk (Polskie Towarzystwo Farmaceutyczne, 2023)
Plant extracts remain an infinite source of bioactive chemicals and an inexhaustible resource for discovering new drugs of natural origin. Thus, in this study, we focused on analysing 29 ethanolic extracts (E1-E29) from selected plants of flora of Poland to assess their antioxidant, anti-inflammatory and acetylcholinesterase inhibitory properties in relation to the chemical profiles of phenolic compounds. The results show that the investigated samples differed in terms of their chemical compositions and biological activities. The extract from Cirsium palustre leaves (E13) possesses the highest phenolic and flavonoid contents as well as antiradical activity in the DPPH (2,2-diphenyl-1-picrylhydrazyl) test (415.28 ± 2.22 µM of Trolox equivalent). On the other hand, the most potent anti-inflammatory agents (at 125 µg/mL) were extracts from Odontites vulgaris herbs (E24), with a COX-2 (cyclooxygenase-2) inhibition percentage of 74.54 ± 0.77, and Erigeron acris flower heads (E22), with a 15-sLOX (soybean 15-lipooxygenase) inhibition percentage of 42.45 ± 3.32. All extracts exhibited moderate acetylcholinesterase inhibitory activity. Moreover, to the best of our knowledge, the present study is the first to report phytochemical and pharmacological analyses of extracts from Anthericum ramosum and Lysimachia europaea.